ANALISIS PREFERENSI NASABAH TERHADAP PRODUK PEMBIAYAAN MURABAHAH DAN MUDHARABAH DI BAITUL MAL WA TAMWIL (BMT) IKHLASUL UMMAH, KABUPATEN BOGOR - Neneng Nurhasanah; Rully Trihantana; Ria Kusumaningrum (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
Baitul Mal wa Tamwil or abbreviated as BMT is an Islamic financial institution based on the Al-Qur'an and Al-Hadith which refers to the principle of muamalah. One of the products that customers are most interested in is murabaha and mudharabah financing products. In deciding to choose and use a financing product, it is influenced by customer preferences through several factors such as psychological factors, personal factors, and social factors. The purpose of this study was to determine the factors that influence customer preferences for financing murabahah and mudharabah contracts at BMT Ikhlashul Ummah Bogor Regency, and to analyze customer preferences for financing murabahah and mudharabah contracts at BMT Ihklashul Ummah Bogor Regency. This research is a qualitative research that uses a descriptive analysis approach with an inductive mindset that takes specific statements and then draws general conclusions. Thus, it can be known the customer preferences in using murabahah and mudharabah contract financing at BMT Ikhlashul Ummah, Bogor Regency.